(untitled) (Лучшие интеллектуальные исследования, 2025)
Annotation. The article is devoted to the issues of improving the mechanisms of informational risk insurance in the national insurance market. In a situation of increasing rapid digitalization and threats to cyber security, ensuring the security of Informationism is becoming one of the pressing problems. Proposals and recommendations will also be developed aimed at improving the efficiency and reliability of the insurance system. Particular attention will be paid to the introduction of innovation insurance products, improvement of risk assessment methods and approaches based on public-private partnership. through the insurance industry, the expected results to be achieved are described.